Bilateral agreement for the academic year 2013-2014 Erasmus within the Lifelong Learning Programme between Universidade Lusíada de Lisboa and Universitat Autònoma de Barcelona - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme (Erasmus); - Subject area: Tourism, catering, hotel management.